2022
DOI: 10.1039/d2ee01458k
|View full text |Cite
|
Sign up to set email alerts
|

Determining overpotentials for the oxidation of alcohols by molecular electrocatalysts in non-aqueous solvents

Abstract: Molecular electrocatalysts for energy-related transformations offer unique opportunities to elucidate mechanistic principles that contribute to improved rates and energy efficiency. New catalysts for electrochemical alcohol oxidation in non-aqueous conditions have...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 57 publications
(100 reference statements)
1
22
0
Order By: Relevance
“…Consistent with previous mechanistic studies, this can be attributed to base-promoted formation of the TEMPO + /alkoxide adduct . A linear Tafel plot obtained for this process is shown in Figure S3B ( E ° PrCHO/PrCH 2 OH = −0.762 V vs Ag/AgCl at pH 13).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with previous mechanistic studies, this can be attributed to base-promoted formation of the TEMPO + /alkoxide adduct . A linear Tafel plot obtained for this process is shown in Figure S3B ( E ° PrCHO/PrCH 2 OH = −0.762 V vs Ag/AgCl at pH 13).…”
Section: Resultssupporting
confidence: 88%
“…At a higher pH, efficient voltage-assisted catalytic oxidation of ethanol occurs at the TEMPO-modified GCE (Figure A). Figure S3C shows the corresponding Tafel plot ( E ° CH 3 CHO/CH 3 CH 2 OH = −0.767 V vs Ag/AgCl at pH 13). Similar to water oxidation voltammograms (Figure B,C), the apparent current density of ethanol oxidation at a TEMPO CNE (Figure B) is 2–3 orders of magnitude higher than that at a TEMPO GCE (Figure A) due to the higher density of TEMPO molecules attached to the porous carbon layer.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the latest advance showed that the participation of water could facilitate the protonation of OOH* as the proton source in alkaline electrolyte and further promote the leave of H 2 O 2 , leading to higher 2e-ORR selectivity and H 2 O 2 yield. 46…”
Section: Catalytic Mechanism and Methods For Performance Evaluation O...mentioning
confidence: 99%
“…Proposed catalytic cycle for oxidation of 2-propanol by Ir­(PNP)­(H) 2 , where PNP is bis­[2-diisopropyl­phosphino)­ethyl]­amide, in the presence of the phenoxyl radical mediator. Reproduced from ref with permission from the Royal Society of Chemistry.…”
Section: Recent Examples Of Redox Mediators In Homogeneous Co-electro...mentioning
confidence: 99%